Darapskite solubility in basic solutions at 25 °C: A Pitzer model for the NaNO3SO4OHH2O system. (March 2017) - Lach, Adeline; André, Laurent; Lassin, Arnault
Abstract: We propose a set of Pitzer interaction parameters to describe the chemical behavior of the Na2 SO4 NaNO3 NaOHH2 O quaternary system at 25 °C. With these parameters we have been able to adequately predict the properties of Na2 SO4 NaNO3 H2 O, Na2 SO4 NaOHH2 O and NaNO3 NaOHH2 O ternary and Na2 SO4 NaNO3 NaOHH2 O quaternary systems, including the solubility of different single salts and the double salt darapskite (Na2 SO4 ·NaNO3 ·H2 O), a mineral that is expected to form in the matrix of some radioactive waste containers. We also successfully reproduced the osmotic coefficient, the water activity and the mean activity coefficients for the Na2 SO4 H2 O, NaNO3 H2 O and NaOHH2 O binary systems. We obtained the set of Pitzer parameters using a step-by-step modeling approach. First, we investigated the binary systems: the NaOHH2 O and Na2 SO4 H2 O binary system interaction parameters were established in previous studies from heat capacity and osmotic coefficient data. Among the various chemical models proposed in the literature that describe the properties of the NaNO3 H2 O binary system, we chose the full dissociation hypothesis, since it allowed complete description of the system with the minimal number of interaction parameters. Next, from the mineral solubility data, we determined the specific interaction parameters for ternary systems. Without further parameterization, the solubility of the various salts in the quaternary system could be reproduced accurately. Highlights: The complex NaNO3 SO4 OHH2 O system is described over the whole range of concentrations. This chemical system is of interest for nuclear waste storage applications. The proposed model provides new ternary Pitzer interaction parameters. The solubility of darapskite and other salts is correctly reproduced in highly alkaline systems. Results of the model suggest new darapskite solubility measurements are needed at high pH.